Translation to practice of cultural safety education in nursing and midwifery: A realist review. (March 2022) - Wilson, Cath; Crawford, Kimberley; Adams, Karen
Abstract: Objectives: Health inequities exist for racial groups as a result of political, societal, historical and economic injustices, such as colonisation and racism. To address this, health professions have applied various health education pedagogies to equip learners to contribute better to cultural safety. The aim of this realist review was to provide an overview of cultural safety programs that evaluate transition of learning to practice to generate program theory as to what strategies best translate cultural safety theory to practice for nurses and midwives. Design: A systematic review following realist review publication standards. Data sources: Nine papers were selected from six databases, from inception to January 2020. Any article that evaluated nurses and midwives practice change following participation in cultural safety education programs was included. Review methods: A realist review was undertaken to refine cultural safety education program theory. This involved an initial broad search of literature, research team consultation, systematic literature search with refinement of the inclusion criteria. For each included article the context, mechanism and outcomes were extracted and analysed. Results: Three program theories resulted. Firstly, system and structural leadership to drive the change process, including adoption of policy and accreditation standards and involvement of the community impacted by health inequity. Second critical pedagogy to reveal institutional and individual racist behaviours and third, nurse and midwife commitment to cultural safety. Conclusion: Change in practice to achieve cultural safety is complex, requiring a multi-system approach. Cultural safety education programs adopting critical pedagogy is necessary for critical consciousness building by nurses and midwives to have impact. However, this is only one part of this interdependent change process. Involvement of those communities experiencing culturally unsafe practice is also necessary for program effectiveness. Further research is required to examine the effectiveness of coordinated multi-system approaches, alongside, nurse and midwife commitment for cultural safety.